2013
DOI: 10.2337/db12-0314
|View full text |Cite
|
Sign up to set email alerts
|

Fetal PGC-1α Overexpression Programs Adult Pancreatic β-Cell Dysfunction

Abstract: Adult β-cell dysfunction, a hallmark of type 2 diabetes, can be programmed by adverse fetal environment. We have shown that fetal glucocorticoids (GCs) participate in this programming through inhibition of β-cell development. Here we have investigated the molecular mechanisms underlying this regulation. We showed that GCs stimulate the expression of peroxisome proliferator–activated receptor-γ coactivator-1α (PGC-1α), a coregulator of the GCs receptor (GR), and that the overexpression of PGC-1α represses genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 52 publications
(71 reference statements)
5
40
1
1
Order By: Relevance
“…When PGC-1␣ is overexpressed in ␤ cells, mice are glucose-intolerant with impaired insulin secretion in response to glucose, which is associated with a decreased ␤-cell mass and ␤-cell hypotrophy. Surprisingly, PGC-1␣ overexpression during fetal life is only enough to induce ␤-cell dysfunction in adults, with no changes in ␤-cell mass, thus suggesting that fetal PGC-1␣ overexpression programmes ␤-cell dysfunction [122]. In contrast, PGC-1␣ overexpression in adults has no effect on glucose homoeostasis and insulin secretion, suggesting that adult ␤ cells are less influential than fetal ␤ cells.…”
Section: Pgc-1α In Pancreatic β Cellsmentioning
confidence: 96%
See 2 more Smart Citations
“…When PGC-1␣ is overexpressed in ␤ cells, mice are glucose-intolerant with impaired insulin secretion in response to glucose, which is associated with a decreased ␤-cell mass and ␤-cell hypotrophy. Surprisingly, PGC-1␣ overexpression during fetal life is only enough to induce ␤-cell dysfunction in adults, with no changes in ␤-cell mass, thus suggesting that fetal PGC-1␣ overexpression programmes ␤-cell dysfunction [122]. In contrast, PGC-1␣ overexpression in adults has no effect on glucose homoeostasis and insulin secretion, suggesting that adult ␤ cells are less influential than fetal ␤ cells.…”
Section: Pgc-1α In Pancreatic β Cellsmentioning
confidence: 96%
“…As several tissues, such as liver, have shown that PGC-1␣ is stimulated by GCs and fasting, and as PGC-1␣ is a coregulator of GRs, the potential involvement of PGC-1␣ in the inhibitory effect of GCs on ␤ cells was studied. It was found that GCs in ␤ cells increase PGC-1␣ expression and that PGC-1␣ forms a complex with GRs to inhibit expression of Pdx1, a crucial ␤-cell transcription factor [122]. An inducible model of mouse pancreatic ␤ cells overexpressing PGC-1␣ (PGC-1␣-Ins) was then developed [122], and revealed that the overexpression of PGC-1␣ is under the control of regulatory elements of the mouse insulin 1 gene and influenced by doxycycline administration.…”
Section: Pgc-1α In Pancreatic β Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est le cas dans le modèle précité où il a été démontré que les hormones glucocorticoïdes jouaient un rôle prépondérant dans les anomalies observées [29,30]. La Figure 2 montre comment l'utilisation de techniques sophistiquées, comme la génération de souris mutantes et l'immunoprécipitation de la chromatine, a permis de comprendre les méca-nismes à l'origine du phénotype obtenu après restriction alimentaire, d'identifier la cellule cible -la cellule pré-curseur -, et finalement le gène cible, Pdx-1 (pancreatic and duodenal homebox 1), un facteur déterminant dans le développement des cellules bêta [29,30].…”
Section: La Preuve Expérimentale Par Les Modèles Animauxunclassified
“…However, preventing the increase in corticosterone in the foodrestricted dams restores the fetal β-cell mass, while reducing the exposure to GC augments the β-cell mass two-fold, increasing mean islet size and islet number (Blondeau et al 2001). Gestational caloric restriction decreases the number of neurogenin 3 (Ngn3)-positive endocrine progenitor cells in fetal rats, partially due to the elevation in corticosterone , which represses several genes important for β-cell development and function via peroxisome proliferatoractivated receptor-c coactivator 1a (PGC-1α) expression (Valtat et al 2013). Accordingly, pregnant rats treated with Dex during the last week of gestation have a reduced β-cell mass and, if Dex treatment is extended for the whole pregnancy, fetal islet vascularization and β-cell proliferation are also reduced (Shen et al 2003, Dumortier et al 2011.…”
Section: The Hpa Axis In Metabolic Programming During Developmentmentioning
confidence: 99%